USING THE OPPORTUNITIES OF FREELANCER PLATFORMS IN FORMING STUDENT’S FREELANCE COMPETENCIES - Xalikov Akbar Tilavberdiyevich (International Scientific and Current Research Conferences, 2023)
This article presents proposals and recommendations regarding the use of freelancing platforms in the formation of freelancing competencies of general secondary school students.